Management of partial anomalous pulmonary venous connections in patients requiring pulmonary resection: a case report and systematic review - Singhal, Kieran; Newton, Andrew D.; Corbett, Christopher; Predina, Jarrod D. (Journal of Thoracic Disease; Vol 9, No 12 (December 29, 2017): Journal of Thoracic Disease, 2017)
Partial anomalous pulmonary venous connections (PAPVCs) are rare congenital anomalies that are frequently asymptomatic in adults. When PAPVCs are encountered in the patient requiring pulmonary resection, improper management can result in fulminant right-heart failure and death. In this report, we note our management of a 70-year-old male who presented with a right upper lobe ground-glass opacity (GGO) and a PAPVC. We also provide a systematic review of all contemporary reports and provide an algorithm for PAPVC management in the adult patient requiring pulmonary resection.